2018
DOI: 10.1016/j.actbio.2018.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cellular mechanisms for zoledronic acid-loaded magnesium-strontium alloys to inhibit giant cell tumors of bone

Abstract: In clinics, giant cell tumors of bone (GCTB) are removed by surgery. However, the resultant defects in bone still contain aggressive and metastatic GCTB cells that can recruit osteoclasts to damage bone, leading to new GCTB tumor growth and bone damage after tumor surgery. Hence, it is of high demand in developing a material that can not only fill the bone defects as an implant but also inhibit GCTB in the defect area as a therapeutic agent. More importantly, the molecular and cellular mechanism by which such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Our study has established that the tumor cell death caused by the contact with the samples of the alloy was due to the induction of apoptosis. Similar conclusions were drawn in a study of the mechanism of cell death during incubation with other magnesium alloys . By employing phenotype Annexin V(+) PI(−) cells, we demonstrated that after 2–3 days of incubation with WE43, a significant part of the tumor cells, while still retaining signs of viability, was at an early stage of apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…Our study has established that the tumor cell death caused by the contact with the samples of the alloy was due to the induction of apoptosis. Similar conclusions were drawn in a study of the mechanism of cell death during incubation with other magnesium alloys . By employing phenotype Annexin V(+) PI(−) cells, we demonstrated that after 2–3 days of incubation with WE43, a significant part of the tumor cells, while still retaining signs of viability, was at an early stage of apoptosis.…”
Section: Discussionsupporting
confidence: 87%
“…ZA decreases the expression of RANK to inhibit the differentiation of osteoclasts through suppressing TNF-α and RANKL [ 39 41 ]. In addition, it is reported that ZA also inhibits NFATc1 and c-fos [ 17 , 26 , 42 ], suppresses NF-κB pathway through promoting the deubiquitination of TRAF6 [ 18 ], as well as the phosphorylation of tyrosine and the nuclear translocation of p65 [ 43 ].
Fig.
…”
Section: Inhibition Of Differentiation Of Osteoclasts By Zamentioning
confidence: 99%
“…M-CSF promotes survival and proliferation of osteoclast precursors, and their differentiation into mature phagocytes, including osteoclasts [ 51 , 52 ]. ZA inhibits the activity, aggregation and migration of osteoclast precursor cells and macrophage [ 17 , 20 , 43 , 53 ] to prevent the differentiation of osteoclasts and induce apoptosis [ 54 ]. It is demonstrated that in the presence of M-CSF, ZA also inhibits RANKL-induced upregulation of RANK mRNA to suppress the differentiation of osteoclasts [ 41 ].…”
Section: Inhibition Of Differentiation Of Osteoclasts By Zamentioning
confidence: 99%
See 1 more Smart Citation
“…Bone defect healing is an intricate but methodical process that restores bone integrity and represents an intrinsic capacity of bone tissue . Most bone defects are repaired spontaneously, while the healing process can be complicated owing to insufficient regeneration when pathological states occur, such as severe trauma, osteoporosis, and bone tumors . Drug therapy is one of the main options for many diseases and is also suitable for the treatment of bone defects.…”
Section: Introductionmentioning
confidence: 99%